Role of computed tomography‐calculated intraparenchymal tumor volume in assessment of patients undergoing partial nephrectomy. (8th February 2018) - Tiwari, Raj Vikesh; Ho, Chia Ming; Huang, Hong Hong; Ho, Henry Sun Sien; Sim, Allen Soon Phang
Abstract : Objectives: To determine the complexity of renal masses by using an objective novel imaging parameter (intraparenchymal tumor volume) based on computed tomography scans, to correlate this parameter to perioperative outcomes and to the RENAL nephrometry score. Methods: After institutional review board approval, 87 patients who underwent partial nephrectomy between 2012 and 2016 at Singapore General Hospital, Singapore, were retrospectively analyzed. Preoperative computed tomography intravenous pyelogram scans were reviewed by a single senior radiologist who calculated the intraparenchymal tumor volume. Once the intraparenchymal tumor volume scores were obtained, they were compared with perioperative renal and surgical outcomes, and nephrometry scores. Furthermore, intraparenchymal tumor volume was subdivided into two categories, low and high intraparenchymal tumor volume, both using the 89th percentile. Results: The mean patient age was 60 years, and the mean tumor size was 2.9 cm. The mean nephrometry score was 7.8, and the mean intraparenchymal tumor volume score was 12.7 cm³. The cut‐off for high intraparenchymal tumor volume was >27.26 cm³. As a continuous variable, intraparenchymal tumor volume showed a significant relationship with the percentage of creatinine change ( P = 0.009) and nephrometry scores ( P < 0.001). As a categorical variable, high intraparenchymal tumor volume showed significance when compared with absolute creatinine change ( P = 0.018), percentage of creatinine change ( P = 0.004) and nephrometry score ( P < 0.001). Conclusions: Intraparenchymal tumor volume represents a novel objective tool based on computed tomography imaging to determine the complexity of a renal mass. This tool correlates with renal functional outcomes of partial nephrectomy, and it also shows good correlation with RENAL nephrometry score.